Antimicrobial Activity of Lavender Essential Oil from Lavandula angustifolia Mill.: In Vitro and In Silico Evaluation - Sylvia Stamova; Neli Ermenlieva; Gabriela Tsankova; Emilia Georgieva (Antibiotics)
The increasing prevalence of antimicrobial resistance (AMR) demands novel strategies, including the use of plant-derived agents. This study investigates the chemical profile and in vitro antimicrobial activity of essential oil from Lavandula angustifolia (LEO), cultivated in Northeastern Bulgaria. Gas chromatography–mass spectrometry (GC-MS) analysis confirmed the presence of a linalool/linalyl acetate chemotype, characteristic of high-quality lavender oil. LEO demonstrated significant inhibitory activity against Escherichia coli ATCC 25922, with minimum inhibitory concentration (MIC) and minimum bactericidal concentration (MBC) values of 0.31% (v/v) and moderate to weak activity against other Gram-positive and fungal strains. Time–kill assays revealed a concentration-dependent bactericidal effect on E. coli. The addition of LEO at subinhibitory concentrations increased the inhibition zones for all antibiotics. In silico analysis identified functional protein clusters potentially modulated by LEO constituents, including targets related to membrane integrity and metabolic regulation. The findings indicate the potential of lavender essential oil as a natural antimicrobial adjuvant; however, additional in vivo and clinical investigations are necessary to validate its therapeutic use. Furthermore, molecular docking analysis revealed a high binding affinity of linalool and linalyl acetate towards the FabI protein of E.coli, suggesting a potential inhibitory mechanism at the molecular level.